2010
DOI: 10.1016/j.matdes.2009.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbon nanotubes reinforced epoxy as adhesives to join aluminum plates

Abstract: Carbon nanotubes (CNTs), a new form of pure carbon, have an extremely unique and desirable combination of mechanical, thermal and electrical properties. The CNT reinforced polymer composites have the potential to meet the electrical and mechanical requirements of various industries. In this paper, CNT reinforced epoxy adhesives was developed. Firstly, the distribution of the carbon nanotubes in the polymer matrix, which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…Various applications of this technology include the repair of cracking, localised reinforcement after removal of corrosion damage and reduction of fatigue strain [1]. Aerospace, automotive, construction, defence and marine are some of the industries that use this technology [2]. Adhesive bonded technology produces plane surfaces without discontinuities and eliminates stress concentrations produced by mechanical fasteners.…”
Section: Introductionmentioning
confidence: 99%
“…Various applications of this technology include the repair of cracking, localised reinforcement after removal of corrosion damage and reduction of fatigue strain [1]. Aerospace, automotive, construction, defence and marine are some of the industries that use this technology [2]. Adhesive bonded technology produces plane surfaces without discontinuities and eliminates stress concentrations produced by mechanical fasteners.…”
Section: Introductionmentioning
confidence: 99%
“…The halloysite particle can adopt a variety of morphologies, but the most common form is an elongated hollow tubular structure with a large aspect ratio, similar to that of carbon nanotubes (CNTs), due to its structural defects, particularly in layer stacking of the neighbouring alumina and silica layers, and their hydrated waters [1]. In recent years, halloysite particles have been investigated as an alternative type of additive for polymers [2][3][4][5][6][7][8][9][10], because halloysite particles are readily obtainable and are much cheaper than other nanoparticles such as CNTs [11,12]. More importantly, the unique crystal structure of halloysite nanotubes resembles that of CNTs, and therefore halloysite particles may have the potential to provide cheap alternatives to expensive CNTs because of their tubular structure in nano-scale.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, CNTs with high level of dispersion are often labelled the definitive fiber (nanofiber) for reinforcement of any type of matrix, including the polymeric one, as seen in Figure 6 that shows the morphology of 5 wt. % of CNT-filled epoxy adhesive [41]. It can be observed that CNTs are dispersed quite homogenously in the epoxy, with only a few small aggregated bundles enhanced by the mechanical stirring followed by ultrasonication preparation method.…”
Section: Carbon Nanotubesmentioning
confidence: 99%